THE IMPORTANCE OF USING DICTIONAIES IN MOTHER TONGUE PRIMARY CLASSES OF PRIMARY SCHOOLS (Archive of Conferences, 2020)
The purpose of this article is to examine the importance of using dictionary in mother tongue classes of primary schools, to be more precise in 1-4 classes